Risk Factors for Clinical Seizures in Neonates with Hypoxic–ischemic Encephalopathy Treated with Therapeutic Hypothermia - Bor, Meltem; Ilhan, Ozkan; Karaca, Meryem; Calik, Mustafa (Klinische Pädiatrie, 2022)
Background This study aimed to assess the risk factors for clinical seizures in newborns treated with whole body cooling (WBC) for hypoxic ischemic encephalopathy (HIE).Methods Infants with gestational age≥36 weeks and birth weight≥2.000 g who were treated with WBC due to HIE were retrospectively enrolled in this study. Patients were assigned to two groups: infants without clinical seizures (Group 1) and infants with clinical seizures (Group 2). The two groups were compared to determine the risk factors for the occurrence of clinical seizures.Results A total of 25 patients (Group 1=10 and Group 2=15) were included in the study. Prothrombin time (PT) was determined as independent risk factor for clinical seizures (p=0.046) and the odds ratio for the effect of PT was found as 1.475 (%95 CI:1.006–2.299). PT (area under the curve [AUC]=0.764; p=0.041), and increased cardiac troponin-I (cTnI) (AUC=0.935; p=0.002) were found to be significant risk factors for predicting the occurrence of clinical seizures. The optimal PT cut-off value was 22.7 sec, with a sensitivity and specificity of 45.4% and 90%, respectively; as well as positive and negative predictive value of 83.3% and 60.0%, respectively. The chest compression in the delivery room, severely abnormal amplitude integrated electroencephalography and high encephalopathy score were also found risk factors for occurrence of clinical seizures.Conclusion Chest compression in the delivery room, high encephalopathy score, prolonged PT, and increased cTnI are significant factors for clinical seizures in newborns treated with WBC for HIE.
Keywords: Neonate; seizure; hypoxic ischemic encephalopathy; therapeutic hypothermia; risk factors